2010
DOI: 10.1021/jp1038249
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Dynamics of the Excited States of Curcumin in Solution

Abstract: Dynamics of the excited singlet (S(1)) state of curcumin has been investigated in a wide varieties of solvents using subpicosecond time-resolved fluorescence and absorption spectroscopic techniques. As a consequence of extra stability of the cis-enol conformer due to the presence of an intramolecular hydrogen bond, it is the major form existing in the ground-state and the excited-state processes described here has been attributed to this form. Steady-state absorption and fluorescence spectra suggest significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
124
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(140 citation statements)
references
References 86 publications
16
124
0
Order By: Relevance
“…In addition to the growth components, the ESA signals of curcumin in MeOH show a single decay component with a time constant τ 3 of 116 ps (51%), as previously reported. 40,47 The decay component in the ESA signal of curcumin in MeOD-d 4 results in a time constant τ 3 of 231 ps, showing a significant deuterium isotope effect of 2.0. This decay component is related to ESIHT, as previously investigated using femtosecond fluorescence upconversion spectroscopy.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the growth components, the ESA signals of curcumin in MeOH show a single decay component with a time constant τ 3 of 116 ps (51%), as previously reported. 40,47 The decay component in the ESA signal of curcumin in MeOD-d 4 results in a time constant τ 3 of 231 ps, showing a significant deuterium isotope effect of 2.0. This decay component is related to ESIHT, as previously investigated using femtosecond fluorescence upconversion spectroscopy.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…In addition to the timescale of ESIHT, there have been some debates on whether the excited-state hydrogen atom transfer reaction of curcumin is intramolecular or intermolecular in nature in polar protic solvents. 41 47 Although it appears that there are two different pathways, these two proposals are in fact very similar, if not identical. This is because the intramolecular pathway proposed by Adhikary et al actually involves interactions of curcumin with the polar protic solvent, which is consistent with the conclusions drawn by Kasha and Maroncelli on the ESIHT reactions of 3-hydroxyflavone and 7-azaindole, respectively.…”
Section: ■ Introductionmentioning
confidence: 99%
“…[14][15][16][17] In particular, previous work has demonstrated that solvent reorganization and excited-state intramolecular hydrogen atom transfer (ESIHT) in the keto-enol moiety of curcumin are major relaxation pathways of its excited state. [14][15][16][17] The ESIHT of curcumin exhibits a deuterium isotope effect while solvation remains unaffected. 14,15 In addition to having a low solubility in water, curcumin undergoes rapid degradation.…”
Section: Introductionmentioning
confidence: 99%
“…Most recently, Ghosh et al used subpicosecond time-resolved transient absorption (TA) and fluorescence upconversion spectroscopy to study the excited state dynamics of curcumin, 21 and reached basically the same conclusion as Adhikary et al's regarding the shorter time constant. For the longer time constant, however, they suggested that intermolecular hydrogen bonding between protic solvent and curcumin may sufficiently perturb the intramolecular hydrogen bonding of curcumin.…”
Section: Introductionmentioning
confidence: 72%
“…3 and Table 2 that a non-hydrogen bonding solvent (chloroform) gives a significantly shorter decay time constant τ 2 than hydrogen bonding solvents. It is to be noted that a very fast decay of curcumin in non-hydrogen bonding solvents such as cyclohexane and 1,4-dioxane (each with a time constant of 44 and 55 ps) in earlier studies 18,21 was attributed to the fact that these solvents do not form intermolecular hydrogen bond with curcumin that would have weakened its intramolecular hydrogen bond, which would decrease the rate of its decay through ESIHT.…”
mentioning
confidence: 96%